Embedded indexing with Word. Part 3 – shifting method and field codes for cross-references and page ranges. (1st December 2020) - Greulich, Walter
Abstract : In this third article in a series on the underexploited potential for using Microsoft Word as a tool for embedded indexing, the focus is on what is called the 'shifting method' and the use of the PAGE field within the XE field. It covers the application of these methods to see also cross-references and page ranges. The important search/replace method in this context, the pattern search, is described in detail. The addition of decorations to page references and the automatic conversion of a Word index into an active ebook index are also considered. The first two articles in the series can be found in the June and September 2020 issues of The Indexer (38(2) and 38(3)).